1997
DOI: 10.1111/j.1540-8159.1997.tb03565.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sensitivity and Specificity of Tilt Protocols with and without Isoproterenol in Children with Unexplained Syncope

Abstract: Head-up tilt testing with or without isoproterenol is extensively used in the evaluation of patients with unexplained syncope. However, sensitivity and specificity of tilt protocols with and without isoproterenol have not been clarified in children, due to lack of age matched control subjects. This study was designed to assess and to compare the sensitivity and specificity of tilting alone and tilting in conjunction with isoproterenol. Thirty children with unexplained syncope (group I) and 15 age-matched contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 40 publications
1
19
0
2
Order By: Relevance
“…We report almost equal sensitivity rates for isoproterenol-(78%) and for nitroglycerin-augmented (79%) tilt test. These values lie within the range reported for isoproterenol, 3,8,10,11 whereas the single previous study assessing nitrate-augmented tilt test in a pediatric population reported an almost identical sensitivity of 77.5%. 19 However, we found significantly lower specificity rates for nitroglycerin-compared with isoproterenol-augmented tilt test.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…We report almost equal sensitivity rates for isoproterenol-(78%) and for nitroglycerin-augmented (79%) tilt test. These values lie within the range reported for isoproterenol, 3,8,10,11 whereas the single previous study assessing nitrate-augmented tilt test in a pediatric population reported an almost identical sensitivity of 77.5%. 19 However, we found significantly lower specificity rates for nitroglycerin-compared with isoproterenol-augmented tilt test.…”
Section: Discussionsupporting
confidence: 61%
“…6,7 The specificity of tilt test is satisfactory, but concern has been raised with respect to its low sensitivity. 5,8,9 As a result, isoproterenol is now used as part of the tilt protocol in the majority of centers, 10,11 but its use requires venous cannulation, which may interfere with the diagnostic accuracy of the test. 12 Data in children, as well as clinical experience, indicate that such observations may apply to an even larger extent in pediatric patients.…”
mentioning
confidence: 99%
“…Reports on the specificity of tilt-testing in children range from 48% to 100%. [15][16][17][18][19][20] Thus, a positive tilttest may not reliably exclude other conditions. Furthermore, tilt-testing is rarely required to diagnose neurocardiogenic syncope.…”
Section: Discussionmentioning
confidence: 96%
“…It is also widely used in pediatric practice on the basis of adult studies. As Alehan reported, the average time for development of symptoms of syncope with HUT was about 20 minutes [2][3][4] and, therefore, 45min-HUT was recommended in syncopal children when isoproterenol is not used.…”
Section: ■ Which Is a Better Orthostatic Test The As Test Or Hut?mentioning
confidence: 96%
“…In order to increase positive response to HUT, invasive procedure (e. g. isoproterenol infusion) and long-time-load (60-minute HUT) are now applied in adults and children. Alehan reported that sensitivity of 10min-HUT for children with unexplained syncope increased to 76.6 % by infusion of isoproterenol while that of 45min-HUT was 48.5 % [3].…”
Section: Introductionmentioning
confidence: 99%